Education sector development and teacher identity construction: a reflective experience - Lawrent, Godlove (Frontiers in Education, 2024)
IntroductionTanzania, like other developing countries, has adopted numerous educational reforms geared towards addressing challenges rooted in either the colonial or post-colonial educational systems. However, the influence of these reforms on teacher professionalism is seldom studied. This study, therefore, gained insights into how the secondary education expansion policy related challenges affected teachers as teaching professionals.MethodsThe qualitative case study design was adopted in order to capture the holistic overview of the phenomena under exploration. Individual interviews, focus group discussion, and document analysis were utilized for gathering data. The main participants were teachers and school principals who were purposively selected from the Iringa region, Tanzania. The region promptly managed to build at least one secondary school in each ward (i.e., at least two villages) as per the government’s expansion enactment directives.ResultsIt was revealed that the inadequate enactment of the expansion policy adversely affected teachers’ self-beliefs about their own teaching aptitudes, their apathy towards teaching, as well as their social status. These issues undermined successful implementation of the policy itself.DiscussionThe study adds to a growing body of literature around how teachers “construct” what secondary expansion means for them as both effective and ethical professionals.